(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The focus of this study was to evaluate the predictive powers of training, compensations on corporate performance (CP) using Nestlé Nigeria, Plc. Three research questions and a hypothesis were answered and tested. A descriptive research design of survey was used. The population comprised 1084 staff of Nestle Plc. in Ogun State. Seven hundred and fifty (750) staff were then selected as the sample using a purposive sampling technique. Three research instruments were used for data collection: Employees’ Job Training Questionnaire (r = .77), Employees’ Compensation Questionnaire (r = .81), and Corporate Performance Questionnaire (r = .76). Pearson Product Moment Correlation (PPMC) and Multiple Regression Analysis (MRA) were used to answer the three research questions and test the hypothesis at .05 level of significance. Results revealed that there were significant relationships between: on-the-job training and CP (r = 239, ƿ <. 01), off-the-job training and CP (r = .727; p <. 01), employees’ compensation and CP (r = .270, ƿ < .01). Model summary from multiple regression showed that the predictors compositely contributed 56.0% (Adj. R2 = .560) to CP and this was significant (F (4, 726) = 230.053, p <. 05), also Multiple R (.750) indicated an overall relationship of the predictors with the explained variable. It is concluded that the management practices (job training, compensation) enhanced the attainment of corporate performance. It is therefore recommended that organisations should do more of the off-the-job training for employees, by ensuring delivery of new knowledge and skills that are applicable to the operations of the organisation, confirming logistics support, and ensuring compliance with the training needs assessment process.